Assessing the impact of plant genetic diversity in shaping the microbial community structure of Vitis vinifera phyllosphere in the Mediterranean. Issue 1 (1st January 2018) - Singh, Prashant; Gobbi, Alex; Santoni, Sylvain; Hansen, Lars H; This, Patrice; Péros, Jean-Pierre
ABSTRACT: The aerial surface of the plant (phyllosphere) is the habitat of complex microbial communities and the structure of this microbiome may be dependent on plant genetic factors, local environment or interactions between them. In this study, we explored the microbial diversity present in the phyllosphere of a very diverse set of grapevine cultivars representing the three genetic pools of the species, grown on an experimental plot at Montpellier (French Mediterranean region). We assessed microbiome variation in the phyllosphere using amplicon sequencing of the 16S rRNA gene and of the internal transcribed spacer (ITS), according to the grapevine genetic pools or cultivars, and organs (i.e. leaves and grape berries). The observed microbiome was complex; out of 542 bacterial genera; Pseudomonas, Pantoea, Sphingomonas, and Acinetobacter were the most abundant and almost ubiquitously present across the samples, and out of 267 fungal genera; Aureobasidium, Alternaria, Mycosphaerella and Aspergillus were most represented. Our results illustrated that the microbial taxa were almost uniformly distributed among the genetic pools and only a few cultivar or genetic pool level differences were found, but a very clear differential taxa abundance was found between the leaf and berry samples. Some genus level associations were also observed with certain genetic pools.